Analisis Strategi Bisnis Coffee Shop Menggunakan Metode Business Model Canvas Dan Quantitative Strategic Planning Matrix (Studi Kasus: Coffee Shop ‘Kopi Dul’) - Nadhira Nurul Muhafi (Journal of Optimization System and Ergonomy Implementation, 2023)
Coffee Shop Kopi Dul is a Coffee Shop that has been established since 2018. The development of Coffee Shop which is getting higher from year to year requires Coffee Shop Kopi Dul to continue to innovate in order to survive amidst competition by mapping business models and creating business development strategies based on internal factors and external. The aim of this research is to plan the development of the Kopi Dul Coffee Shop business using the Business Model Canvas and QSPM methods. The data processing process in this research begins by creating a Business Model Canvas, the input stage is the IFE and EFE matrices, the matching stage is the IE, SPACE and SWOT matrices, the decision stage uses the QSPM method, finally a new Business Model Canvas which has been added to alternative strategies. obtained. The results of the research analysis show that the Kopi Dul Coffee Shop is in a hold and maintain position based on the results of the IE matrix, is in the aggressive quadrant based on the results of the SPACE matrix, and has 8 alternative strategy formulations based on the SWOT matrix. At the Decision stage, the alternative priority strategy is "Conducting regular competitor observations" with an STA value of 6.371. Next, a proposed Business Model Canvas is created by adding alternative strategy formulations at the matching stage.